2012
DOI: 10.1038/onc.2012.67
|View full text |Cite
|
Sign up to set email alerts
|

Tumor development is associated with decrease of TET gene expression and 5-methylcytosine hydroxylation

Abstract: The TET (ten–eleven translocation) family of α-ketoglutarate (α-KG)-dependent dioxygenases catalyzes the sequential oxidation of 5-methylcytosine (5mC) to 5-hydroxymethyl-cytosine (5hmC), 5-formylcytosine and 5-carboxylcytosine, leading to eventual DNA demethylation. The TET2 gene is a bona fide tumor suppressor frequently mutated in leukemia, and TET enzyme activity is inhibited in IDH1/2-mutated tumors by the oncometabolite 2-hydroxyglutarate, an antagonist of α-KG, linking 5mC oxidation to cancer developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
488
6
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 512 publications
(536 citation statements)
references
References 22 publications
31
488
6
11
Order By: Relevance
“…5-Hydroxymethylation of cytosine bases (5-hmC) is a newly identified epigenetic marker; this nontraditional DNA modification involves methylation of cytosine bases (5-mC) in CpG dinucleotide sequences 2,3 and their oxidation by the ten-eleven translocation (TET) family of proteins. While 5-hmC is a potentially useful indicator of disease states such as cancer [4][5][6][7][8] , the mechanisms controlling its abundance in tumours and its impact on gene expression and cancer cell fate are unclear.…”
mentioning
confidence: 99%
“…5-Hydroxymethylation of cytosine bases (5-hmC) is a newly identified epigenetic marker; this nontraditional DNA modification involves methylation of cytosine bases (5-mC) in CpG dinucleotide sequences 2,3 and their oxidation by the ten-eleven translocation (TET) family of proteins. While 5-hmC is a potentially useful indicator of disease states such as cancer [4][5][6][7][8] , the mechanisms controlling its abundance in tumours and its impact on gene expression and cancer cell fate are unclear.…”
mentioning
confidence: 99%
“…However, like 5mC alterations, the 5hmC patterns undergo considerable changes linked to genome instability (70,71) across several forms of human cancers (72). Recent studies revealed that 5hmC is consistently found at significantly reduced levels (more than 50% reduction, p ≤ 0.01) in various solid tumors (73)(74)(75). Recently, using a mouse model, Pan et al (76) studied the role of hydroxymethylation in neurophysiological processes and provided the first evidence that miRNAs can be regulated by hydroxymethylation of their promoters.…”
Section: Dna Hydroxymethylationmentioning
confidence: 99%
“…27 TET proteins are thought to have a role in tumor development, as inhibition of TET activity, as well as alteration of global DNA methylation, has been demonstrated in multiple tumor types. [28][29][30][31][32] Thus, succinate accumulation in the context of SDH deficiency could potentially drive tumorigenesis via the inhibition of TET family proteins and subsequent changes in DNA methylation and gene expression patterns. Indeed, recent work has shown that siRNA-mediated knockdown of SDHA in cultured cells and in mice leads to an inhibition of TET activity and decreased levels of 5-hmC.…”
mentioning
confidence: 99%